The influence of job embeddedness and organizational commitment on organizational citizenship behavior in BULOG - Haryati, Endri; Widodo, Agus Purbo; Widodo, Teguh Setiawan (Trigin Publisher, 2024)
Job embeddedness means employee engagement in an organization through social networks, namely trust and cohesion. Embeddedness are all factors that involve employees in their work, this can happen if there is a match between work values and individual values and community values with individual values. Organizational commitment is an individual's loyalty to the organization. Those who have high commitment tend to persist more and have lower absenteeism than those who have low commitment. Organizational Citizenship Behavior (OCB) is part of the science of organizational behavior, OCB is a form of work behavior that is usually not visible or taken into account. BULO G is a state-owned public company engaged in food logistics. The company's business scope includes logistics/warehousing business, surveying and eradicating pests, providing plastic sacks, transportation business, food commodity trading and retail business. Based on the results of the analysis and discussion, this research uses Path Diagrams and Hypothesis Testing with the Partial Least Squares (PLS) method using the SmartPLS 3.0 program. Based on this conclusion, Based on these results, it can be said that job embeddedness and organizational commitment have a significant effect on organizational citizenship behavior in BULOG employees.